Effects of Electroacupuncture on Muscle State and Electrophysiological Changes in Rabbits with Lumbar Nerve Root Compression - 孙懿君 吴耀持 张峻峰 张鹏 唐占英 (Chinese journal of integrative medicine, 2013)
Objective： TO observe the effects of electroacupuncture on force-displacement value （FDV） of muscle state and electrophysiology of the muscle in rabbits with lumbar nerve root compression. Methods： Thirty New Zealand white rabbits were randomly divided into a control, a model, an electro-acupuncture acupoints （EAA）, a medication, and an electro-acupuncture un-acupoints （EAU） group. All rabbits except those in the control group were subject to modeling （surgical lumbar nerve root compression）. The control group was sham-operated without nerve root compression. The F_AA group received electro-acupuncture at bilateral Shenshu （BL23） and Dachangshu （BL25） that were located 1.5 cun lateral to the posterior midline on the lower border of the spinous process of the 2nd and 4th lumbar vertebra, respectively. The EA was 15 mm deep and the frequency was 2 Hz. Each session lasted for 20 min per day for a total of 14 times. The medication group was treated with Loxoprofen sodium by gastrogavage at 4 mg/kg per day for 14 days. The EAU group received electro-acupuncture identical to the EAA group with regard to the treatment frequency and duration except a different acupoint at the tip of rabbit tail. Muscle states were determined by measuring FDVs of the bilateral biceps femoris using the Myotonometer fast muscle state detector. Meanwhile, the prolonged and non-prolonged insertion potentials were measured by electromyography before and after modeling and after treatment. Latency, amplitude （Amp） of evoked potential, motor nerve conduction velocity （MNCV） were also determined after treatment. Results： （1） After modeling, FDVs of right side activation （RSA, P=0.003） and right side relaxation （RSR） in the model group （P=0.000） were significantly decreased in comparison to the control group. The number of rabbits with non-prolonged insertion potentials in the model group was also significantly decreased （P=0.015） in comparison to the control group. （2） After treatment, FDVs of RSR were significantly increased in the EAA （P=0.000） and medication groups （P=0.018） in comparison to the model group. The increase in FDVs of RSR in the EAA group was significantly higher than that in EAU （P=0.000） and medication groups （P=0.002）. MNCV in the model group was reduced compared with the control group （P-=O.000）. The reduction in MNCV after modeling was reversed in the EAA group （P=0.000） and medication group （P=0.008） after treatment and the increases were significant in both treatment groups in comparison to the model group. The EAA group had a greater MNCV recovery than the medication group （P=0.022）. Conclusion： Electro-acupuncture could improve the rehabilitation and regeneration of FDVs and the electrophysiology index of the muscle with nerve control impairment.